Formulasi Tablet Hisap Ekstrak Teh Hijau (Camellia sinensis L. Kuntz) dengan Penambahan Vitamin C atau Ekstrak Biji Anggur (Wtis vinifera L.) dan Uji Aktivitas Antioksidannya - SWASONO R. TAMAT; LEONARDUS B.S. KARDONO; DEWITA AGUS (JURNAL ILMU KEFARMASIAN INDONESIA, 2010)
Formulation of lozenges containing: A) green tea extract; B) green tea extract with sodium ascorbate; and C) green tea extract with grape seed extract have been carried out. Antioxidant activities were compared to the activity of raw active materials. Lozenges were tested for physical characteristics, hedonic values, dissolution rate, and stability during storage, Physical tests indicated that the lozenges comply with the Farmakope Indonesia IV requirements. Determination of IC50 antioxidant activity using DPPI-I free radical scavenger showed that IC50 of formula A, B, and C were 844.04 µg/mL, 221.80 µg/ mL, and C 57.4 µg/mL, respectively. Meanwhile, IC50 value of green tea extract, sodium ascorbate, and grape seed extract were 4.29 µg/mL, 12.95 µg/mL, and 1.96 µg/ml., respectively. Accelerated stability test were carried out based on the EGCG concentration observed by using HPLC and then calculated by Arrhenius equation showed that the shelf life of lozenges of formula A, B, and C Were 2,11 years; 1.87 years; and 2,73 years, respectively. The result showed that the lozenge containing green tea extract and grape seed extract (formula C) is the best formula based on FI IV requirements, antioxidant activity and lozenges stability.